Herbicide resistance: Implications of climate change on the susceptibility of weeds to herbicides – A review - Ofosu, Rita (Acta Agraria Debreceniensis, 2026)
Climate change is a major issue in agricultural sustainability posing severe problems that threaten global food security. Conventional farming often utilizes herbicides to control weeds in most management strategies. In recent times, transformations in weeds due to shifts in climatic conditions across the globe are making management strategies in many ecosystems more complex. Climate variables including high carbon dioxide concentrations, increased temperature levels and altered moisture conditions affect many plants physiology. In weed species, a change in climate conditions can impact growth of weeds and the effectiveness of herbicides used in controlling the weeds. Therefore, there is the need for changes to be made with production practices to reduce emissions and to adapt to a changing climate in agriculture to limit the negative impact of weeds. The aim of this perspective is to deliver insights on herbicide application, describe the effects of climate on weed biology and development, and highlight the necessity to synthesize this information for establishing a long-term framework for sustainable weed management.